Microbiological analysis of raw milk, pasteurized milk and yogurt samples collected from different areas of Dhaka city, Bangladesh (Journal of Bangladesh Academy of Sciences, 2015)
A total of 300 different milk and yogurt samples were collected from Dhaka city and analyzed for total viable bacterial count (TVBC), total coliform count (TCC) and presence of several pathogens such as Escherichia coli, Salmonella spp., Shigella spp., Vibrio spp. and Listeria monocytogenes. Raw milk samples collected from Moghbazar area showed highest TVBC (4.2 × 106 cfu/ml) and samples from Mohammadpur area showed lowest count (3.5 × 103 cfu/ml). All the pasteurized milk samples showed TVBC of 1.9 × 102 to 2.8 × 103 cfu/ml, and TCC only in one sample Yogurt samples (open) collected from vendor showed TVBC of 9.1 × 103 to 8.2 × 107 cfu/ml, and TCC only in sample collected from Dhanmondi, Dhaka. The packed yogurt samples showed TVBC of 2.2 × 102 to 6.1 × 103 cfu/ml, and TCC only in one sample. All the milk and yogurt samples were found contaminated with E. coli and Shigella-like species. Listeria monocytogenes was not detected in any of the samples studied.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 31-36, 2015